Regulated polarization of active particles in local osmotic flow fields - Lisa Rohde; Desmond Quinn; Diptabrata Paul; Frank Cichos (Communications Physics)
Abstract Regulation of a well-defined target state is essential for reliable functionality in living systems and maintaining non-equilibrium states. Controlling properties of microscale systems is particularly challenging due to thermal fluctuations and environmental disturbances. While synthetic active matter shows self-organization capabilities, examples of autonomous regulation at the single-particle level are rare. We demonstrate that two non-equilibrium processes create a regulated polarization state of active particles in local osmotic flow fields. The balance between thermophoretic repulsion and attraction by thermo-osmotic boundary flows, both generated by a single heat source, creates a steady state where active particles circle the heat source at a distance dependent on the source temperature. This balance results in particle polarization independent of heat source temperature. Individual control of heat source and active particles allows a detailed study of this self-regulated polarization effect, revealing dominant hydrodynamic interactions. Since these effects rely on osmotic flows and phoretic interactions, we expect these phenomena can be applied to other active systems and flow fields.